Pattern of occlusal contacts in intercuspal position of natural teeth - Imran, Tanzeela; Ahmed, Naseer; Nazeer, Bushra (Journal of Oral and Dental Sciences, 2016)
The purpose of this study was to determine the patterns of occlusal contacts and location in intercuspal position of natural teeth. A cross-sectional study was conducted with a sample size of around seventy patients within a span of seven months, complete mouth impressions were made of each patient with hydrocolloid material and the impressions were poured in dental stone. The contact areas of the teeth in the maximum intercuspation position were determined by wax. Three distinct types of indentations were noted on the wax interocclusal record. Then similarly the centric occlusion contacts of the teeth on the cast were determined by interposing a new piece of wax, approximating the casts in the maximum intercuspation position by hand, and applying pressure. The oral and cast wax recordings were then compared. The occlusal relation for each individual tooth was then classified and recorded in a Performa. Following wax interocclusal record of natural teeth in intercuspation an ideal occlusion was absent, a difference in morphology of anterior and posterior teeth was also evident that inevitably affects the nature of occlusal contacts. The ideal occlusion was not found in any of the patient’s investigation.